Recuperación y articulación efectiva del Parque la Rebeca y Palacio De Los Niños en la ciudad de Neiva-Huila (2022)
The objective of this study is to strategically articulate the Palacio de los Niños and La Rebeca parks, through innovation and sustainable development; con sidering the great importance of the population and the projections of the municipality. Since this sector currently represents a focus of insecurity in a recreational area sponsored by the absence of a sense of belonging of the community of NeivaHuila, i t is essential to present the community with comprehensive alternatives to their problems. The research has been developed by means of a mixed methodology, that is to say, the implementation of both quantitative and qualitative data. The main techniques u sed were surveys, field diaries and social mapping, to obtain qualitative data; at the same time, different studies previously conducted by entities such as Finter, applications such as WAZE, among others, were implemented to obtain quantitative data, whic h allowed us to know the needs of the population, and the relationship of these with the projections recommended and/or planned by governmental entities.